The weaponisation of artificial intelligence in modern warfare: Implications for global peace and security - Osimen, Goddy Uwa; Fulani, Oluwakemi Morola; Chidozie, Felix; Dada, Dolapo Omolara (Research Journal in Advanced Humanities, 2024)
The integration of Artificial Intelligence (AI) into military operations has significant implications for global stability. Understanding these implications is crucial for policymakers, researchers, and the international community. This study addresses the impact of AI-driven technologies on defence systems. It examines autonomous weapons, surveillance, and cyber warfare, highlighting the potential for an arms race. The main argument is that responsible AI deployment is essential for maintaining peace and security. The study is anchored on Deterrence theory. This study adopts qualitative research methods as a means of data collection which is secondary source based, and were merely obtained from textbooks, Journal articles, conference proceedings, Newspapers, and reliable internet materials. The data collected were analysed thematically. The study however revealed that AI enhances military capabilities while raising legal and ethical concerns. The study therefore recommends among others, the need for AI governance via international norms, and cooperation to prevent misuse.